GAMBARAN DERAJAT DISMENOREA (NYERI HAID) DAN UPAYA PENANGANAN PADA REMAJA PUTRI USIA 13-15 TAHUN DI SMPN 2 TEMBILAHAN HULU - Mia Rita Sari (STIKES HUSADA GEMILANG, 2019)
Dysmenorrhea is pain during menstruation, it usually happens with cramps and is found in the lower abdomen. The pain intensity of dysmenorrhea on teenagers is vary. In Indonesia, the percentage of dysmenorrhea is 64.25%. The treatments can be completed in combination (nonpharmacological and pharmacological treatments). The study drives the description of thedysmenorrhea intensity and the treatments on teenagers ages 13-15 at SMPN 2 Temblahan Hulu. The research is descriptive qualitative with a simple random sampling technique. The population of the research were 163 the students (grade VIII and IX of SMPN 2 Tembilahan Hulu) and 115 respondents for the sample, but only 81 respondents meet the criteria. The data of the research were gained through the use of the questionnaire. The results prove that there were 41 respondents (50.6%) – mild pain, 33 respondents (40.7%) – moderate pain, and (8.7%) – severe pain; there were 65 respondents (80.3%) – non-pharmacological treatment, 13 respondents (16.0%) – combination treatment (non-pharmacological and pharmacological), and 3 respondents (3.7%) – pharmacological treatment. It is likely to supply the dysmenorrhea material and its treatments to PIK organization, so it becomes a referral forum for those who met dysmenorrhea in order to have better understanding about the dysmenorrhea intensity and its treatments.